2015
DOI: 10.1002/adsc.201500744
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Metal and Organic Catalysis: Highly Diastereo‐ and Enantioselective Construction of Fluorinated 2‐Aminocyclopenta[b]pyran Derivatives

Abstract: An efficient highly diastereo-and enantioselectivep rotocolt oa ccess optically pure fluorinecontaining2 -amino-cyclopenta[b]pyran derivatives using Lewis acid catalysisa nd organocatalysiss equence has been developed. Thec orresponding productsc ould be obtained in good to excellent yields with good to excellent diastereoselectivity and enantioselectivity (up to 99:1 dr, > 99% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…So it will be very interesting to develop an efficient protocols to access the optically pure fluorine‐containing 2‐aminopyran framework. In order to achieve this goal, an efficient highly diastereo‐ and enantioselective protocol to access optically pure fluorine‐containing 2‐amino‐cyclopenta[b]pyran derivatives 98 from cycloalkenones 96 using Lewis acid catalysis and organocatalysis sequence has been developed in 2015 (Scheme ) . This strategy combines the advantages of Lewis acid catalysts L1 and squaramide catalyst I .…”
Section: Squaramide‐catalyzed Asymmetric Cascade Reactionsmentioning
confidence: 99%
“…So it will be very interesting to develop an efficient protocols to access the optically pure fluorine‐containing 2‐aminopyran framework. In order to achieve this goal, an efficient highly diastereo‐ and enantioselective protocol to access optically pure fluorine‐containing 2‐amino‐cyclopenta[b]pyran derivatives 98 from cycloalkenones 96 using Lewis acid catalysis and organocatalysis sequence has been developed in 2015 (Scheme ) . This strategy combines the advantages of Lewis acid catalysts L1 and squaramide catalyst I .…”
Section: Squaramide‐catalyzed Asymmetric Cascade Reactionsmentioning
confidence: 99%
“…Among the different ligands used for catalysis, those containing an oxazoline ring in their structure, specially 2-oxazolines are of outstanding importance, due to their demonstrated activity and efficiency in several catalytic applications. [2] Compared with the 2oxazolines, the 2-thiazolines have been less studied, [3] nevertheless some reports describe that both ligands show remarkable differences in their catalytic performance. [4] On the other hand, in addition to the variety of frameworks used to obtain bidentate ligands, only a few examples contain pyrrole as the main structural motif, [5] which has proven quite efficient compared with its aryl analogues.…”
Section: Introductionmentioning
confidence: 99%
“…The Shibatomi and Iwasa group reported a fluorination reaction using a unique chiral spiro oxazoline ligand L12 , affording products with excellent enantioselectivity (up to 99% ee) . The Du group reported a reaction catalyzed by diphenylamine-linked bis­(thiazoline) L13 –Cu­(OTf) 2 complex; although the substrate scope was very narrow, some products were obtained with up to 99% ee. , Just recently, a reaction using this ligand under solvent-free conditions in a ball mill was also reported . The Xu group examined Ph-BINMOL-derived salan L14 –Cu complex and found that fluorination reaction of 1-indanone-2-carboxylate derivatives proceeded with excellent enantioselectivity (up to 99% ee) .…”
Section: Modern Methods For Construction Of Quaternary C–f Stereogeni...mentioning
confidence: 99%
“…In 2005, Jørgesen reported that ( R , R )-DBFOX-Zn­(ClO 4 ) 2 catalyzed asymmetric fluorination of β-keto phosphonates 210 (Scheme a) . Several other groups also tried asymmetric fluorination catalyzed by a zinc salt with chiral ligands, but in most cases, the enantioselectivity was inferior to that obtained with Cu or Ni catalysts having the same ligands. ,,,, , In 2008, the Shibata and Toru group reported enantioselective fluorination of methyl tert -butyl malonate esters 222 . They first applied their conditions for the asymmetric fluorination reactions of β-keto esters using Ni catalyst to the malonate esters and obtained high asymmetric induction (up to 89% ee).…”
Section: Modern Methods For Construction Of Quaternary C–f Stereogeni...mentioning
confidence: 99%